PENGEMBANGAN BAHAN AJAR BERUPA HANDOUT PADA PEMBELAJARAN AKUNTANSI DASAR FASE F: STUDI ANALISIS TRANSAKSI BISNIS - Romadhon, Anwar; Sari, Septiani Mulya; Hanifah, Nur; Dewi, Retno Mustika; Hakim, Luqman (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
Basic accounting learning in Phase F of the Independent Curriculum is designed to equip students with an understanding of accounting concepts and skills in analyzing business transactions systematically and applicatively. However, practice in the field shows that learning still uses lecture methods and teaching materials that are less contextual, thus inhibiting students' understanding and active involvement (Astuti & Rahmawati, 2017). To overcome this, this study aims to develop teaching materials in the form of handouts as an alternative learning resource that can increase students' involvement and understanding of the company's business transaction analysis material. The study uses a Research and Development (R&D) approach with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The handout was developed based on the needs of Phase F students and contains contextual elements such as real transaction examples, account visualizations, and structured practice questions designed to improve analytical thinking skills. The results of expert validation show that this handout is very feasible to use in learning, with a feasibility score above 80%. Limited trials on grade XI students showed an increase in understanding of concepts and transaction analysis skills, as evidenced by the significant difference in pretest and posttest results (Nisfu Syabana & Susilowibowo, 2022). This finding is in line with the results of other studies which state that contextual teaching materials can improve students' cognitive skills in understanding complex material (Nurmalasari & Ratnawati, 2020).